Hubungan Pengetahuan, Sikap, Dan Riwayat Penyakit Terhadap Penggunaan Metode Kontrasepsi KB Suntik 3 Bulan Di PMB Ny. I Desa Neglasari Kecamatan Cikalong Kabupaten Cianjur Tahun 2022 : Relationship of Knowledge, Attitudes, and Medical History to the Use of the 3-Month Injectable Contraceptive Method at PMB Ny. I Desa Neglasari Village, Cikalong District, Cianjur Regency in 2022 - Maulidah Pratiwi, Rezza Siti (Dohara POAJ, 2023)
Introduction: The number of people of childbearing age continues to increase from year to year, according to the results of the 2020 Population Census. In 1971, the proportion of the population in the productive age group was 53.39 percent of the total population and will increase to 70.72 percent in 2020. rapidly raises complex problems. The purpose of this study was to determine the relationship between knowledge, attitudes, and medical history on the use of the 3-month injection method of family planning at PMB Ny. I Desa Neglasari, Cikalong District, Cianjur Regency in 2022. Methods: The purpose of this study was to determine the relationship between knowledge, attitudes, and medical history on the use of the 3-month injection contraceptive method at PMB Ny. I Desa Neglasari Village, Cikalong District, Cianjur Regency in 2022. The type of research used is quantitative research, using a cross-sectional approach with an analytical descriptive method. The study population consisted of 202 family planning acceptors at PMB Ny. I Desa Neglasari Village period May-June 2022 and a sample of 67 respondents using the sampling technique, namely simple random sampling. Results: Data collection used a questionnaire and data analysis used the chi-square test. The results of the chi-square test analysis showed that if there was a relationship between knowledge and 3-month injection contraceptive use, p-value = 0.002, attitude towards 3-month injection contraceptive use p-value = 0,004; and history of illness with 3-month injection contraceptive use p-value = 0,001 with OR = 0,124 (0,037-0,418). Discussion: The results of the chi-square test analysis showed that there was a relationship between knowledge, attitudes, and medical history with the use of 3-month injectable family planning at PMB Ny. I Desa Neglasari Village in 2022, knowledge p-value = 0.002, attitude p-value = 0,004; and history of disease p-value = 0,001 with OR value = 0,124 (0,037-0,418).